(3GdeUfas - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s ((3GdeOQSI GdTdHjI GdMSGejI s)
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3jfJgj Hef cGf jSJMH Cf jbQC aj GdaLQ jhe GdLeYI s
(3Hg ChQGb eWehSI HSHH GMJQGb GdMHQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B104 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1711s
Keywords: (3GdMOjK h GdeUWdMs